Groundwater recharge estimation using water budget method for Bauru Aquifer system in a Cerrado environmental protection area - Ramires, Thiago [UNESP]; Manzione, Rodrigo Lilla [UNESP] (Univ Estadual Centro-oeste, 2019)
Agrometeorological water budget can be an efficient tool on water resources management and water use plans elaboration. However, different sources of precipitation data and how they are included in the water budget equations can significantly alter the results. In this study were estimated groundwater recharges at Bauru Aquifer System in a Cerrado protection area at Aguas de Santa Barbara/SP-Brazil from different sources of precipitation data obtained by remote sensing satellites, meteorological radar and ground surface climate stations. These data were integrated with systematic hydrological monitoring data from 2014/2015 and land use cover classification data in a model in a geographical information system environment. The spatial analysis of water budget data demonstrate a significant local recharge in the study area, with the percentual volume from precipitation varying from 20.43% using ground surface climate station; 23.67% using precipitation data estimated by Z-R Calheiros radar equation; and 35.54% using TRMM satellite data.
Keywords: monitoring; GIS; geotechnologies; precipitation